Research in transportation economics - McMullen, B. Starr (Jai Press, 1999)
This volume of Research in Transportation Economics reflects the changes that are occurring in the transportation arena as we enter the twenty-first century. In the US, the transportation industries, rail and trucking in particular, are still adjusting to deregulation that has taken place since the 1970's. The emerging transportation issues focus less on economic regulation of the transport sector and more on policies to deal with congestion, optimal pricing, and the allocation of scarce resources. The papers presented represent a diverse view of transportation economics, in a field that is forever changing as regulations change, ecnomic growth continues, and our econometric and modeling methods become increasingly refined.